The Other Function: Class II-Restricted Antigen Presentation by B Cells - Adler, Lital N.; Jiang, Wei; Bhamidipati, Kartik; Millican, Matthew; Macaubas, Claudia; Hung, Shu-chen; Mellins, Elizabeth D. (Frontiers in Immunology, 2017)
Mature B lymphocytes (B cells) recognize antigens using their B cell receptor (BCR) and are activated to become antibody-producing cells. In addition, and integral to the development of a high-affinity antibodies, B cells utilize the specialized major histocompatibility complex class II (MHCII) antigen presentation pathway to process BCR-bound and internalized protein antigens and present selected peptides in complex with MHCII to CD4+ T cells. This interaction influences the fate of both types of lymphocytes and shapes immune outcomes. Specific, effective, and optimally timed antigen presentation by B cells requires well-controlled intracellular machinery, often regulated by the combined effects of several molecular events. Here, we delineate and summarize these events in four steps along the antigen presentation pathway: (1) antigen capture and uptake by B cells; (2) intersection of internalized antigen/BCRs complexes with MHCII in peptide-loading compartments; (3) generation and regulation of MHCII/peptide complexes; and (4) exocytic transport for presentation of MHCII/peptide complexes at the surface of B cells. Finally, we discuss modulation of the MHCII presentation pathway across B cell development and maturation to effector cells, with an emphasis on the shaping of the MHCII/peptide repertoire by two key antigen presentation regulators in B cells: HLA-DM and HLA-DO.